Contextualização do ensino de química por meio do enfoque CTS atrelado à pedagogia de Paulo Freire - Jesus, Maísa Pereira de (2017)
Science education in the Science-Technology-Society perspective (CTS) aims to train a student with a critical conception and to broaden their view on the role of science and technology in society, valuing the interactions between these spheres. Discussing science, technology and society in the classroom encompasses values and attitudes that need to be associated with the conceptual understanding of the subjects of the discipline inherent in social and scientific aspects, in order to favor the decision-making capacity of individuals as citizens. The teaching of CTS presents similarity with the liberating pedagogy of Paulo Freire, when defending a politicized education that stimulates the popular sovereignty. Paulo Freire highlights the use of a "generating theme" as a way of contextualizing teaching. Throughout the process of adult literacy, he proposed the use of generative themes. The teaching of CTS has as its pillar scientific literacy, which is linked to the intention of training the citizen, understood as an individual capable of actively participating in a democratic society, with the ability to defend a point of view, that is, with capacity to Argumentation. In this sense, the development of argumentative practices in the classroom helps the process of scientific literacy. Given these assumptions, this dissertation presents the analysis of the development of a didactic sequence (SD) composed of 8 classes, and in the last two are provided moments of argumentative discussions among students. SD was elaborated from the teaching perspective of CTS and Pedagogy of Paulo Freire, considering the theme-generator "foods". The research sought to verify how the development of SD, in a 3rd year high school class, contributed to the students' argumentative capacity, combining scientific conceptions with social and economic aspects. It was characterized as intervention research, which is a trend of the participating researchers, following a qualitative approach. The data was obtained by filming with two video cameras, one focusing on the whole class, and another, a specific group of students. The data recorded in video were analyzed considering analytical categories focused on the actions of the teacher and in the discussions among the students. For the actions of the teacher were used categories presented by Mortimer and Scott (2003), being: communicative approach, patterns of interaction and intentions of the teacher. Discussions among the students were analyzed considering the Argumentation Pattern of Toulmin (2006). Throughout the SD, the teacher sought to promote an awareness of the students in relation to the industrialized foods, with dyes, preservatives and the consumer society, interrelating the chemical content with the reality of the student, under a critical perspective on the values Capitalists. In order to generate argumentative discussions among the students, the teacher inserted guiding questions. In these moments of discussion, she worked with the intentions of exploring students' points of view and guiding them in the process of internalizing scientific ideas. The communicative approach ranged from interactive / dialogic to interactive / authoritative. The results indicate how the teacher's actions made possible the interactions between the students and the joint elaboration of arguments, which took into account social and technological aspects allied to scientific knowledge. It was also verified the elaboration of a critical look of the students before the industrialized foods in the society of current consumption.